LIMB SALVAGE SURGERY COMPARED TO AMPUTATION IN BONE AND SOFT TISSUE TUMORS: A CRITICAL ANALYSIS OF CURRENT EVIDENCE (Journal of Medical & Health Sciences Review, 2025)
ABSTRACT  Introduction: Bone and soft tissue sarcomas historically required amputation for local control. But the development of imaging, chemotherapy, radiotherapy, and surgical methods means that LSS (limb salvage surgery) becomes a treatment of choice in many cases, so that the tumor can be removed while limb function is retained.Historical Perspective: Until the 1970s, amputation was the mainstay of musculoskeletal oncology treatment, before advancements in diagnostic imaging and systemic therapies made limb salvage procedures possible. Early reports showed equivalent survival after LSS versus amputation, and thus leading toward the change in attitude towards limb salvage.Current Practices and Criteria for Surgical Choice: Selection for surgery is focused on achieving clear margins without impacting function. Limb salvage is recommended when the tumor is localized, without compromising the critical neurovascular bundle, and reconstruction can result in meaningful function. Amputation is still indicated in patients with tumor spread, no response to therapy or unachievable reconstruction. Surgical planning that includes multidisciplinary team assessment and patient's care is crucial.Comparative Analysis of Outcomes: Survival is comparable overall between LSS and amputation with acceptable margins. Functional and psychological results generally favor LSS, and limb salvage is associated with increased rates of complications and possible need for reoperation. Quality of life evaluations tend to describe more favorable results after LSS, when rehabilitative treatment has been successful.Challenges and Limitations: LSS may be associated with increased local recurrence, surgical complications, and economic burdens. Amputation although is more definitive, may result in speedier recovery and fewer reoperations in select cases.Conclusion: Limb sparing surgery has similar oncologic results to amputation and has better functional and quality of life outcomes in selected cases. A personalized and multidisciplinary approach for overall survival and limb function plays a key role in the treatment of bone and soft tissue tumors.